Innovation capabilities and business performance in the smart farm sector of South Korea - Daeyu Kim; Seunghoo Jin (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Ever-increasing unpredictability has led to recognition of increasing importance of innovation capabilities of businesses. In spite of recognizing such an important issue of innovation capability, not much research has been conducted on the relationship between innovation capabilities in business planning, R&D, commercialization and innovation performance. The current research, thus, intends to provide an empirical analysis of the effect of smart farm companies' innovation activities on their innovation performance. Classifying innovation capabilities into three categories of planning, R&D and commercialization capability, the current research aims to identify the effect of each category on sales and patent acquired. Moreover, it aims to identify the moderating effect of governmental policy and support for technology on the relationship between innovation activities and performance. It was found that planning, R&D and commercialization capabilities exerted a positive impact on business performance. It was also found that governmental policies and support helped enhance business performance.
Keywords: 650; innovation capabilities; moderating effect; smart farm; venture companies